CHARACTERISTICS OF HYDROLYSATE PROTEIN FROM MALONG FISH (Congresox talabon) WHICH HYDROLIZED BY USING PAPAIN ENZYME - Defri Ilham; Dewita Dewita; Rahman Karnila (Fakultas Perikanan dan Kelautan, Universitas Riau, 2019)
This study aimed to utilize the fishbone waste from different types of fish, Pangasius sp., Clarias sp., Paraplotosus sp. as high calcium of bone flour and determine the quality characteristics of fishbone flour which was produced. The method used was a non-factorial Completely Randomized Design (CRD), with different types of fish bones as treatments which consisting of 3 levels: Pangasius sp. bone (Tp), Clarias sp. bone (Tl), and Paraplotosus sp. bone (Ts) with 3 replications and 9 units of experimental units. The parameters tested were organoleptic, proximate analysis, calcium, phosphorus, and whiteness degrees. The results showed that the Pangasius sp. bone flour (Tp) was the best treatment with characteristics of brilliant appearance, the distinctive aroma of fish was still felt, smooth and dry texture, as well as whiteness degrees that the best treatment in walking catfish bone flour with value 81.30%, referred to whiteness degrees of flour, it is below the range of 80-90%. Meanwhile, the best proximate value was obtained in Paraplotosus sp. bone treatment (Ts) with moisture, ash, fat, protein, carbohydrate, calcium and phosphorus content was 5.71%, 54.60%, 2.57%, 25.21%, 10.83%, 38.4%, and 33.9%.